Strengthening Research-Education-Extension (R-E-E) Linkage in New Context of Federal Structured Nepal - Mahesh Jaishi (Responsible Education, Learning and Teaching in Emerging Economies, 2020)
Objective: The objective of this paper to examine the major limitations of past efforts in Nepal regarding the link between agriculture research, education, and extension and to highlight the government’s strategy and policy measures to overcome these limitations in the new federal structure in Nepal.